A study on the impact of mentoring on the employment of postgraduate students in Chinese colleges - Jiang, Xue; Wang, Hong (Frontiers in Education, 2025)
Postgraduate student mentoring and postgraduate employment are two pressing challenges in postgraduate education today, and we focus on the relationship between the two in an effort to address both issues. Based on a survey of 725 Chinese postgraduate students, this study explored the relationship between the mentoring and postgraduate employment. Specifically, this study delves into how mentoring influences postgraduate employment satisfaction by enhancing employability, which includes academic competence, personal quality competence, and employment capital. The results show that (1) the mentoring is significantly and positively correlated with the employment satisfaction of postgraduate students, exerting a notable direct effect on their employment satisfaction; (2) academic competence, personal quality competence, and employment capital have a significant mediating effect between the mentoring and employment satisfaction of postgraduate students. In summary, this research highlights the critical role of mentoring in bolstering postgraduate employment satisfaction by fostering the cultivation of employability skills.